Sleep-Mediated Heart Rate Variability after Bilateral Carotid Body Tumor Resection - Niemeijer, Nicolasine D. (Sleep, 2015)
STUDY OBJECTIVES: The carotid bodies are thought to play an important role in sleep-dependent autonomic changes. Patients who underwent resection of bilateral carotid body tumors have chronically attenuated baroreflex sensitivity. These subjects provide a unique opportunity to investigate the role of the baroreflex during sleep. DESIGN: One-night ambulatory polysomnography (PSG) recording. SETTING: Participants' homes. PARTICIPANTS: Nine patients with bilateral carotid body tumor resection (bCBR) (four women, mean age 50.4 ± 7.2 years) and nine controls matched for age, gender, and body mass index. INTERVENTIONS: N/A. MEASUREMENTS: Sleep parameters were obtained from PSG. Heart rate (HR) and its variability were calculated using 30-s epochs. RESULTS: In bCBR patients, HR was slightly but not significantly increased during wake and all sleep stages. The effect of sleep on HR was similar for patients and controls. Low frequency (LF) power of the heart rate variability spectrum was significantly lower in bCBR patients in active wakefulness, sleep stage 1 and REM sleep. No differences were found between patients and controls for high frequency (HF) power and the LF/HF ratio. CONCLUSIONS: Bilateral carotid body tumor resection (bCBR) is associated with decreased low frequency power during sleep, suggesting impaired baroreflex function. Despite this, sleep-related heart rate changes were similar between bCBR patients and controls. These findings suggest that the effects of sleep on heart rate are predominantly generated through central, non-baroreflex mediated pathways. CITATION: Niemeijer ND, Corssmit EP, Reijntjes RH, Lammers GJ, van Dijk JG, Thijs RD. Sleep-mediated heart rate variability after bilateral carotid body tumor resection. SLEEP 2015;38(4):633–639.